Brachial Plexus Formation and Adult Structure - Douglas Gould (Association of American Medical Colleges, 2009)
Abstract Introduction This resource is a multimedia module aiming to simplify the study of brachial plexus structure and function. The module uses a combination of novel illustrations, animations, clinical photographs, explanatory text, and a set of printable questions to provide an easy-to-understand tutorial for the brachial plexus. Methods The course of each of the five terminal branches of the brachial plexus is illustrated and accompanied by a general pathway description. Muscles receiving motor innervation from each terminal branch are listed and shown diagrammatically in a separate set of images. Posed and real clinical photographs and descriptions are included with each terminal branch to illustrate the result of nerve lesion. In addition, the cutaneous patterns of sensory innervation are illustrated. The program requires either a Macintosh or PC with Quicktime 3.0. Results Student evaluations of the program highlight its ease of use as well as clear and intuitive navigation. Student evaluations also validated the use of illustrations and animations as beneficial to understanding and retention of the material. Survey results indicate the program is useful in helping students in their study of the brachial plexus. Discussion One of the most beneficial aspects of the program is a simple animation showing the development of the brachial plexus from its embryological origins that illustrates limb rotation and the resulting adult anatomy and dermatomal arrangement.